Preliminary analyses of radionuclides in Afsin-Elbistan lignite samples - (:unkn) unknown (SPRINGER, 2000)
This preliminarly study describes the concentration of radionuclides U-238, Th-232, K-40, and Ra-226 in Afsin-Elbistan lignite samples which are primarily used for power generation in the Afsin-Elbistan Coal-Fired Power Plant. The results show that the concentration of U-238 is higher in the Afsin-Elbistan lignite compared to various world coals whereas the opposite is observed with Th-232 and K-40.
Keywords: FIRED POWER-PLANTS; RAY-FLUORESCENCE ANALYSIS; NATURAL RADIONUCLIDES; RADIOACTIVITY MEASUREMENTS; COAL; ELEMENTS; ASHES; TURKEY